PENERAPAN MODEL PROBING-PROMTING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS IV SDN 139/1 SUNGAI BULUH - Oktavia Andriani; Eka Sastrawati; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the application of the Probing-Prompting learning model in improving the critical thinking skills of fourth grade students in learning Natural and Social Sciences (IPAS). The Probing-Prompting model is a method that is oriented towards exploring concepts through questions directed to students, which aims to stimulate their thinking power to be more analytical and reflective. The research method used in this study is classroom action research (PTK), which was carried out in two cycles with the research subjects of grade IV students of SDN 139/1 Sungai Buluh. The research data was collected through observation, interviews, and learning outcome tests to assess the development of students' critical thinking before and after the application of this learning model. The results showed that the application of the Probing-Prompting model can significantly improve students' critical thinking skills as shown through several indicators, including simple explanation, basic skill building, ability to conclude, and providing further explanation.